Cluster Analysis of the Transport and Logistics Potential of the Regions of Kazakhstan - A. A. Satybaldin; B. E. Sadykov; A. T. Moldabekova; Z. B. Akhmetova (Экономика: стратегия и практика)
The purpose of this study is to assess the regional transport and logistics potential considering economic indicators for transport and logistics. Based on the literature review, elements of the transport and logistics infrastructure were identified, and the mutual influence of the development of transport and logistics and the country’s economy was substantiated. The study of methodological approaches made it possible to identify indicators for assessing the country’s regional transport and logistics potential. We identified 11 indicators in the following groups: indicators of transport infrastructure, logistics indicators and economic indicators for transport and warehousing. The database was generated in the context of regions and cities of republican significance for 2021 according to statistical data from the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan. Using the cluster analysis method, regions were ranked, and groups of regions with different levels of transport and logistics potential were identified. Recommendations were made to improve the quality of logistics services along international transport corridors in the regions of Kazakhstan. The necessity of technological modernization of the transport and logistics infrastructure of the region is substantiated, which allows the creation of modern conditions for the effective functioning of all components of the transport and logistics infrastructure of the region.